Anion Immobilization Enabled by Cation‐Selective Separators for Dendrite‐Free Lithium Metal Batteries. (1st March 2022) - Zhao, Qing; Zhou, Rongkun; Wang, Chengjie; Kang, Jianxin; Zhang, Qianqian; Liu, Jingbing; Jin, Yuhong; Wang, Hao; Zheng, Zilong; Guo, Lin
Abstract: The lithium dendrite issue is a major bottleneck that limits the utilization of lithium metal anodes in high‐energy rechargeable batteries. From the perspective of the dendrite nucleation mechanism, this work develops a new type of cation‐selective (CS) separator with anion immobilization behavior to boost the lithium metal anode. By taking advantage of the poly(vinylidene fluoride) matrix, a strong binding force with anions contributes to an excellent CS property of the separator, which is further confirmed by molecular dynamics simulations. The CS separator developed in this work presents a high lithium‐ion transference number up to 0.81. Considering such a dramatically reduced transference number of anions, it can prolong the nucleation time of lithium dendrite and thus achieve a high‐stable Li plating/stripping cycling for 1000 h at a high applied current density of 3 mA cm −2 . The Li metal stabilization function of the CS separator is further studied in detail through both in‐situ and ex‐situ observations of dendrites growth. When integrating into lithium metal batteries (LMBs), the CS separators also contribute to enhanced electrochemical performances including discharge capacity, rate capability, and cycling durability. This work is anticipated to provide considerable insight for the creative design of CS separators toward dendrite‐free LMBs. Abstract : A robust large‐area cation‐selective (CS) separator is developed for constructing dendrite‐free lithium metal batteries (LMBs). The CS separator can effectively immobilize anions within the liquid electrolyte, which contributes to an extreme long‐term reversible and stable Li plating/striping without dendrite deposition at a high current density. Furthermore, the CS separator also boosts the electrochemical performance of LMBs.